Nutritional calcium supply dependent calcium balance, bone calcification and calcium isotope ratios in rats - Rott, Jeremy; Töpfer, Eva Teresa; Bartosova, Maria; Kolevica, Ana; Heuser, Alexander; Rabe, Michael; Behets, Geert; D’Haese, Patrick C.; Eichwald, Viktoria; Jugold, Manfred; Damgov, Ivan; Zarogiannis, Sotirios G.; et al. (International journal of molecular sciences, 2022)
Serum calcium isotopes (δ44/42Ca) have been suggested as a non-invasive and sensitive Ca balance marker. Quantitative δ44/42Ca changes associated with Ca flux across body compartment barriers relative to the dietary Ca and the correlation of δ44/42CaSerum with bone histology are unknown. We analyzed Ca and δ44/42Ca by mass-spectrometry in rats after two weeks of standard-Ca-diet (0.5%) and after four subsequent weeks of standard- and of low-Ca-diet (0.25%). In animals on a low-Ca-diet net Ca gain was 61 ± 3% and femur Ca content 68 ± 41% of standard-Ca-diet, bone mineralized area per section area was 68 ± 15% compared to standard-Ca-diet. δ44/42Ca was similar in the diets, and decreased in feces and urine and increased in serum in animals on low-Ca-diet. δ44/42CaBone was higher in animals on low-Ca-diet, lower in the diaphysis than the metaphysis and epiphysis, and unaffected by gender. Independent of diet, δ44/42CaBone was similar in the femora and ribs. At the time of sacrifice, δ44/42CaSerum inversely correlated with intestinal Ca uptake and histological bone mineralization markers, but not with Ca content and bone mineral density by µCT. In conclusion, δ44/42CaBone was bone site specific, but mechanical stress and gender independent. Low-Ca-diet induced marked changes in feces, serum and urine δ44/42Ca in growing rats. δ44/42CaSerum inversely correlated with markers of bone mineralization.
Gesehen am 07.07.2023